Structural remodeling activates bacterial anti-phage immunity: insights from HerA-DUF4297 - Wang, Xiaoyan; Zhang, Leiliang (Frontiers in Cellular and Infection Microbiology, 2025)
In response to phage infection, bacteria have evolved a variety of sophisticated immune defense systems to combat viral predation. Among these defense mechanisms, the transmission of immune signals via intracellular signal transduction molecules is a common strategy that often accompanies enzyme activity. Recent studies have characterized the HerA-DUF4297 protein complex, a two-component defense system that integrates ATPase and nuclease activities. This complex inhibits phage infection by inducing DNA degradation. Notably, DUF4297 displays minimal nuclease activity when it operates on its own. However, it demonstrates robust nuclease activity when in complex with HerA. Crucially, the nuclease activity within this complex is regulated by structural changes. These findings provide novel insights into the activation of bacterial immune systems against phages, suggesting that the architectural remodeling of protein complexes can serve as a mechanism for transmitting immune signals.